Substance use in pregnancy: The medical challenge - Louw, Kerry-Ann (Obstet Med, 2018)
Substance use contributes significantly to the global burden of disease. Growing numbers of women use nicotine, alcohol, and illicit substances. Women are the most vulnerable to problematic substance use in their reproductive years. The first 1000 days of life, starting at conception, have been established as a critical window of time for long-term health and development. Substance use in pregnancy is associated with negative pregnancy and child health outcomes. The impact of antenatal substance use on these outcomes needs to be considered within a challenging and complex context. This review provides an overview of the current literature on the impact of substances on pregnancy and child outcomes as well as the evidence and guidelines on screening and interventions for women using substances during pregnancy.